- PROSES BERFIKIR KRITIS SISWA SMP DALAM BERKARYA ILUSTRASI MURAL BERTEMA BHINEKA TUNGGAL IKA - Ulil Amri, Deva; Sabri, Indar; Juwariyah, Anik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to analyze and describe the critical thinking process of junior high school students in creating mural illustrations with the theme of Bhinneka Tunggal Ika. This study describes whether critical thinking occurs in the activities carried out with six indicators, including interpretation, analysis, evaluation, inference, explanation, and self-regulation. The method used in this study is descriptive qualitative. The study employs several worksheets to assist students in carrying out the project activities. The research subjects are limited to seventh-grade students at SMPN 2 Jetis Mojokerto. The results of the study on the mural illustration activity themed “Bhinneka Tunggal Ika” indicate that the project can assist in the critical thinking process. However, the limitations of the study have not quantitatively explained the accurate range of improvement in the critical thinking process, necessitating further follow-up.